Impact of paraaortic lymphadenectomy for endometrial cancer with positive pelvic lymph nodes: A Korean Radiation Oncology Group study (KROG 13-17). Issue 10 (October 2016) - Yoon, M.S.; Park, W.; Huh, S.J.; Kim, H.J.; Kim, Y.S.; Kim, Y.B.; Kim, J.-Y.; Lee, J.-H.; Kim, H.J.; Cha, J.; Kim, J.H.; Kim, J.; et al.
Abstract: Aim: We investigated the role of paraaortic lymph node dissection (PALND) in patients with stage IIIC1 endometrial carcinoma after surgery followed by adjuvant radiotherapy (RT) alone or chemoradiotherapy (CTRT). Methods: We performed a subgroup analysis in 151 patients treated with adjuvant pelvic RT. Paraaortic-recurrence free survival, disease-free survival (DFS) and overall survival (OS) were analyzed. Results: In adjuvant RT alone, PALND was significantly related to reduced risk of paraaortic recurrence (0% vs. 17.1%) and distant metastasis (4.5% vs. 19.5%) compared with the no PALND group. PALND affected 5-year DFS (90.2% vs. 58.9%, p = 0.016) and OS (100% vs. 83.1%, p = 0.022). For the CTRT group, the paraaortic recurrence rate was 19.5% for the no PALND group and 12.8% for the PALND group (p = 0.682). Of patients who underwent PALND in the CTRT group, less extensive PALND was significantly related to increased paraaortic recurrence (≤10 vs. >10 dissected LNs, 17.1% vs. 0%). In the no PALND group (n = 82), 5-year paraaortic-recurrence free survival was 79.4% for the CTRT group and 76.2% for the RT alone group (p = 0.941). In multivariate analysis, PALND was significantly associated with reduced risk of disease-specific death (HR, 0.50; 95% CI, 0.26–0.96; p = 0.037). Conclusion: PALND provided excellent paraaortic control and improved outcome in stage IIIC1 endometrial cancer with favorable tumor features treated with adjuvant RT alone. Less extensive PALND was associated with significantly increased paraaortic recurrence in patients with advanced tumor features treated with adjuvant CTRT. Combined CTRT did not affect disease control in the paraaortic region compared with RT alone.